CORRELATION BETENGAN TRADITIONAL GAMES ON LOCOMOTOR MOVEMENTS AND CHARACTERS - Pratiwi, Ika Ari; Kuryanto, Mohammad Syaffruddin (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2019)
The purpose of this study is to determine the positive correlation between traditional games with student movements and friendly characters.The study was conducted at SD Muhammadiyah 1 Kudus. Research methods using a quantitative correlational approach. The research sample consisted of 29 students. This research technique is collecting observation data, analyzed using Pearson product-moment correlation test with prerequisite linearity and normality tests.The results showed that the data met the prerequisite test with a significance of linearity of 0.898 and the significance of normality of 0.20. Obtained results of the coefficient significance of traditional game betengan with the locomotor motion of 0.708> 0.5 and with a very strong correlation category level. On the other hand, there is a significant coefficient of correlation betengan traditional games with friendly characters of 0.702> 0.05 with a very strong level. So the results of traditional game betengan research have a strong correlation with locomotor motion and student-friendly character.